Experimental investigation on flexural fatigue performance of recycled aggregate concrete hybrid with basalt-polyacrylonitrile fiber - Chuheng Zhong; Qipeng Xiao; Zuwei Fan; Weiqi Mao; Sijia Xing; Jinhui Chen; Yuan Xiao; Jinzhi Zhou (Scientific Reports)
Abstract To reduce the construction industry’s reliance on raw natural resources and alleviate the environmental pressures caused by waste concrete, recycling waste concrete materials as recycled coarse aggregate in the production of new concrete presents a viable solution. This study aims to expand the application of recycled aggregate concrete (RAC) in road and bridge engineering. In this experiment, twelve concrete mixtures were designed to investigate the effects of basalt fiber (BF) and polyacrylonitrile fiber (PANF) on the performance of RAC. Based on the flexural strength test, flexural fatigue tests were conducted at various stress levels. Weibull distribution theory was employed to analyze the fatigue life of fiber-doped RAC. Single logarithmic and double logarithmic fatigue equations were developed to predict the ultimate fatigue strength of the specimens. The test results indicated that BF and PANF significantly enhanced both the flexural strength and fatigue life of RAC, with the most notable improvement observed in the mixture containing 0.1% BF and 0.15% PANF. The Weibull theory effectively analyzes the fatigue life with a good fit, and the double logarithmic fatigue equation yields better predictions than the single logarithmic equation.